Pengaruh gaya kepemimpinan transformasional, kompetensi, dan pengembangan karir terhadap kinerja pegawai melalui kepuasan kerja di fraksi PKB DPR RI - Efendi, Suryono; Fiton, Moch. Khusnul (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to analyze the influence of transformational leadership style, competence, career development, on employee performance through job satisfaction in the PKB faction of the DPR RI. The type of research used is quantitative research. The research sample of 110 employees was selected by the Simple Random method. Data collection using questionnaires and Structural Equation Modeling (SEM) was used as an analysis technique. The results of the study prove that the variables of transformational leadership style, competence, career development have a positive and significant effect on employee performance through job satisfaction. The results of the study have implications for transformational leadership style, competence, career development which have a positive influence on performance so that it can be concluded that transformational leadership, competence, career development need to be improved in order to improve employee performance..